Mali : Requests for Disbursement Under the Rapid Credit Facility and Rephasing of Access Under the Extended Credit Facility Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Mali. (IMF Staff Country Reports; Country Report, 2020)
This paper discusses Requests for Disbursement Under the Rapid Credit Facility (RCF) and Rephasing of Access Under the Extended Credit Facility (ECF) Arrangement. The coronavirus disease 2019 (COVID-19) shock hit the economy hard amid an already challenging social and security situation. The decline in economic activity, spillovers from global trade and financing shocks, along with fiscal measures to combat the crisis have created an urgent balance-of-payments and fiscal financing needs. The authorities have responded quickly to the pandemic with containment measures, stepped up healthcare response, and emergency measures to support households and business affected by the outbreak. The regional central bank responded with measures to support liquidity in the banking system. Given the urgent balance of payment need caused by the COVID-19 pandemic and the infeasibility of completing a review under the ECF arrangement, staff supports these requests and welcomes commitments to safeguard transparency and accountability in the use of emergency funds. The RCF is expected to cover about 40 percent of the financing gap in 2020 and is expected to play a catalytic role. The authorities are actively engaged with other donors, including the World Bank, to cover the remaining financing needs.